Dialektika Affinitas Dan Konsanguinitas Dalam Pewarisan Perdata Terhadap Kedudukan Anak Tiri - Rayi Kharisma Rajib; Dina Amalia; Salsabila Khammalatal Falakhah (JURNAL ILMIAH NUSANTARA, 2026)
This study aims to analyze the dialectic between affinity (due to marriage) and consanguinity (blood relationship) in civil inheritance law in Indonesia, particularly regarding the position of children in a second marriage after divorce. The research method used is normative juridical with a regulatory and contextual approach, supported by primary, secondary, and tertiary legal materials through literature review. The results of the study indicate that in the inheritance system based on the Civil Code, consanguinity is the main basis for determining heirs, as regulated in Article 832 and Article 852 of the Civil Code, while affinity is only recognized to a limited extent by the longest surviving husband or wife. As a result, stepchildren in a second marriage do not have the status of heirs ab intestato because they do not have a blood relationship with the testator. However, stepchildren are still allowed to obtain a share of the property through other legal mechanisms such as gifts or wills while still paying attention to the provisions of legitime portie. Thus, there is tension between the social reality that recognizes kinship in stepfamilies and legal provisions that emphasize biological relationships, necessitating preventive legal measures to provide certainty and justice in inheritance distribution.